The effect of childhood trauma on serum BDNF in bipolar depression is modulated by the serotonin promoter genotype. (24th August 2017) - Benedetti, Francesco; Ambrée, Oliver; Locatelli, Clara; Lorenzi, Cristina; Poletti, Sara; Colombo, Cristina; Arolt, Volker
Highlights: Evidence is increasing that adult BDNF levels are influenced by childhood trauma. We found that early trauma and the short form of the serotonin promoter transporter were negatively associated with BDNF serum levels in adult patients with bipolar depression. Possible mechanisms include epigenetic modulation of BDNF gene expression, due to different reactivity to stressors in 5-HTTLPR genotype groups. Abstract: In healthy humans, both childhood trauma and the short form of the serotonin promoter transporter genotype (5-HTTLPR) are associated with lower levels of brain-derived neurotrophic factor (BDNF). In subjects with bipolar disorder (BD), lower levels of BDNF and a higher degree of childhood trauma were observed compared with healthy controls. However, is still unknown if the functional 5-HTTLPR polymorphisms exerts an effect on both abnormalities. In 40 inpatients affected by a major depressive episode in the course of BD, we genotyped 5-HTTLPR, measured serum BDNF with ELISA, and assessed early adversities by the childhood trauma questionnaire (CTQ). Data were analyzed in the context of the general linear model correcting for age, sex, ongoing lithium treatment, severity of current depression, and CTQ minimization/denial scores to investigate the effect of 5-HTTLPR polymorphism and childhood trauma on BDNF levels. Early trauma were negatively associated with BDNF serum levels (higher CTQ scores, lower BDNF; p = 0.0019). 5-HTTLPR l/l homozygotes showed significantly higher BDNF levels than 5-HTTLPR*s carriers (30.57 ± 6.13 vs 26.82 ± 6.41; p = 0.0309). A separate-slopes analysis showed that 5-HTTLPR significantly influenced the relationship between early trauma and adult BDNF (interaction of 5-HTTLPR with CTQ scores: p = 0.0023), due to a significant relationship between trauma and BDNF in 5-HTTLPR*s carriers, but not among l/l homozygotes. Putatively detrimental effects of childhood trauma exposure on adult BDNF serum levels are influenced by 5-HTTLPR genotype in patients affected by BD. Possible mechanisms include epigenetic modulation of BDNF gene expression, due to different reactivity to stressors in 5-HTTLPR genotype groups.